A new cleaner species of Elacatinus (Actinopterygii: Gobiidae) from the Southwestern Atlantic - Sazima, Ivan; Carvalho-Filho, Alfredo; Sazima, Cristina (Zootaxa, 2008)
A new species of cleaner goby, Elacatinus phthirophagus sp. n., is described from Fernando de Noronha Archipelago, off northeastern Brazil. It differs from its congeners of the putative “randalli-evelynae” cleaning clade by the following combination of characters: mouth subterminal, pale (bright yellow in life) elliptical spot on dark snout, width of lateral pale (bright yellow in life) stripe almost equal as eye diameter (slightly narrower in live individuals), light purplish sheen (in life) extending laterally from below eye to tail origin, no blue line (in life) from below eye to end of opercular margin, teeth multiserial on the distal portion of both jaws, males with 3 enlarged and recurved teeth on dentary inner row. The new species was recorded at depths ranging from 3 to 18 m and is ubiquitous in the archipelago islets. It tends cleaning stations on coral heads, sponges, and rocky substrata, with up to 15 individuals present in large stations, particularly those on sponges. Elacatinus phthirophagus sp. n. was recorded to clean about 30 species of fish clients, including large carnivores such as the shark Carcharhinus perezi and smaller carnivores such as the grouper Cephalopholis fulva, besides small clients like the planktivorous damselfish Chromis multilineata and the zoobenthivorous butterflyfish Chaetodon ocellatus. The new species increases to three the number of cleaner gobies recorded for Southwestern Atlantic, one from the coast and two from oceanic islands.